2002
DOI: 10.4141/s01-003
|View full text |Cite
|
Sign up to set email alerts
|

N2 fixation by soybeans grown with different levels of mineral nitrogen, and the fertilizer replacement value for a following crop

Abstract: fixation by soybeans grown with different levels of mineral nitrogen, and the fertilizer replacement value for a following crop. Can. J. Soil Sci. 82: 139-145. A field experiment was established to study the impact of added mineral N on the prediction of N 2 fixation by soybean, and the consequences for the nature of any N credit that might be used to modify fertilizer recommendations to a following non-fixing crop. Nodulating and non-nodulating isolines of soybean were grown with five rates of N fertilizer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…While the average proportion of N 2 fixed by soybean plants in this study (60%) is similar to literature values (Unkovich and Pate 2000;Goss et al 2002), we observed significant variability in both the % N from fixation and total N 2 fixed across these fields. Both biomass production and the relative reliance on N 2 fixation contributed to the nearly 6-fold variation we observed in total N 2 fixed across the 13 fields at the end of the growing season.…”
Section: Variability In Soybean Nitrogen Fixationsupporting
confidence: 81%
See 3 more Smart Citations
“…While the average proportion of N 2 fixed by soybean plants in this study (60%) is similar to literature values (Unkovich and Pate 2000;Goss et al 2002), we observed significant variability in both the % N from fixation and total N 2 fixed across these fields. Both biomass production and the relative reliance on N 2 fixation contributed to the nearly 6-fold variation we observed in total N 2 fixed across the 13 fields at the end of the growing season.…”
Section: Variability In Soybean Nitrogen Fixationsupporting
confidence: 81%
“…This contrasts with results from fertilizer-based field studies and hydroponic greenhouse experiments, which have consistently reinforced the concept that soil N availability is the dominant edaphic regulator of BNF (e.g., Hardarson et al 1984;Streeter 1985;Waterer and Vessey 1993;Goss et al 2002). Field experiments usually are carried out in the same field and N availability is manipulated across a relatively constant background soil environment (Boller and Nosberger 1994;Goss et al 2002). We found that N 2 fixation was impacted by both the direct suppressive effect of soil N availability and other soil properties, such as soil texture that may indirectly impact N 2 fixation via oxygen and water saturation dynamics.…”
Section: Agroecosystem Contextmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, numerous greenhouse and field experiments have shown that increasing inorganic N reduced nodulation and legume N 2 fixation (e.g., Van Kessel and Hartley , Goss et al. , Salvagiotti et al. ).…”
Section: Discussionmentioning
confidence: 99%